(untitled) (Community Based Medical Journal, 2026)
A prospective, cross-sectional study was conducted in the Department of Nephrology, Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, from January to December of 2024, to determine the prevalence of cardiovascular disease in patients with chronic kidney disease (CKD). A purposive sample of 113 adult patients having CKD (Stages 3-5) was enrolled in this study. Data on socio-demographics, clinical history, and biochemical parameters were collected. Cardiovascular disease was defined and assessed based on clinical history, ECG findings, and echocardiographic evidence. The overall prevalence of cardiovascular disease was 78.8%. Left ventricular hypertrophy was the most common manifestation (64.6%), followed by congestive heart failure (42.5%) and ischemic heart disease (31.9%). A significant association was found between advancing CKD stage and CVD prevalence (p<0.001). Patients with CVD exhibited significantly lower hemoglobin and ejection fraction, and higher serum creatinine, urea, and potassium levels (p<0.001), highlighting a profound cardiorenal interplay. Our study reveals an alarmingly high prevalence of cardiovascular disease in CKD patients, dominated by left ventricular hypertrophy. Integrated cardiorenal care and aggressive management of risk factors from early CKD stages are imperative to reduce associated morbidity and mortality. CBMJ 2026 January: vol. 15 no. 01 P:183-188